Uwagi na temat charakteru prawnego dyrektywy wymiaru kary za ciąg przestępstw. Część I - Kokot, Rajnhardt (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
The article considers the problem of punishment for the series of crimes. It raises the legal character of the rule of tightening the criminal responsibility as a consequence of committing crimes remaining in a confluence of events connected with the buckle of continuity. The main doubt accompanying such evaluation is connected with the answer to the question if the legal effects within the scope of punishment resulting from the art. 91 § 1 of the Penal Code express ordinary or extraordinary punishment. The dispute about the legal nature of the consequences resulting from that regulation has not only the theoretical-legal dimension. Accepting one of those options causes far-reaching legal consequences within the sphere of the application of the law practice. It decides about the scope of the legal responsibility and determines the relations with other statutory premises that modify its limits. In this context there are also the remarks considering the conditions of accepting the set of principles, resulting from art. 57 of the Penal Code, reforming those limits with the rule of punishment for the series of crimes. The analysis taken in the elaboration takes up the problem of the punishment for the continuous act defined in art. 12 of the Penal Code. Taking into consideration that this institution derives from the same, as the series of crimes, structure of the continuous act of crime that was in the Penal Code from 1969 the basis of the extraordinary tightening the punishment, there comes the question, whether resigning from modifying the principles of legal responsibility for the continuous act of crime can lead to an impression of the dissymmetry of penalty of both structures is the reasonable and rational solution.
Keywords: seria; zbieżność wydarzeń; zaostrzenie; przestępstwo; kara; zakres geograficzny zatwierdzenia GMO; odpowiedzialność; wielość; ciągłość; modyfikacja; dyrektywa